Joaquim Catunda e a recepção do debate evolutivo na segunda metade do século XIX - Monteiro, Nivia Marques (2014)
This present paper attempts to analyze the scientific conceptions of Joaquim Catunda (1834 - 1907) with the aim of understanding the reception of evolutionary ideas and racialist in the second half of the nineteenth century, like Darwinism and other evolutionary theories. Intellectual and political, Catunda was born in Ceará, author of Estudos de História do Ceará (1886), one of the founders of the Historical Institute of Ceará and Senator. Throughout the second half of the nineteenth century, the evolutionary debate addressed issues such as the origin of man and the debates between science and religion. By analyzing the writings of Catunda, specifically Estudos de História do Ceará, we identified a clear evidence of the interest of Catunda by studies of these issues, including the antiquity of American man, the chances of peopling of America, supported by evolutionary assumptions and other theories sought to explain the emergence and development of man. In this sense, the focus of our discussion are the theoretical matrices of Catunda, analyzed through their intellectual production of historiographical nature, in order to problematize the appropriation of these ideas by the author and understand how evolutionary ideas allied to the historiographical discourse were interpreted while studied its political and intellectual trajectory.